Plan to bear fruit: frutaformas internationalization to the United Kingdom - Vyhovska, tetyana (2019)
Frutaformas is a Portuguese micro-enterprise, specialized in the production of premium dehydrated-fruit, an emerging snack category fostered by the increasing trend for healthier alimentary habits in developed countries. The relatively small size of the domestic market and the growing competition led Frutaformas to consider Europe as an attractive for export market. A scoring model based on a set of macro and micro-level criteria suggested the United Kingdom as the preferential target country at this stage. Recommendations on the entry mode and the associated risks were elaborated taking into account the country and industry analysis as well as Frutaformas’ unique organizational platform.